2016
DOI: 10.1016/j.pec.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Improving the understanding of schistosomiasis among adolescents in endemic areas in Brazil: A comparison of educational methods

Abstract: Objective To evaluate the effectiveness of two teaching strategies, both guided by the concept of dialogicity, on adolescents’ knowledge about schistosomiasis and adherence to diagnostic fecal testing. Methods Two teaching strategies related to schistosomiasis were developed, an educational video and group conversation, which were tested in two groups of students aged 10–15 years old. Before and after the intervention, a questionnaire was applied to assess participants' knowledge about schistosomiasis and, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Through the implementation of schistosomiasis health education session, the cognition level of schistosomiasis among primary and secondary school students was significantly improved, and the effect on primary and secondary school students was quite. This suggested that This interactive mode health education has a positive effect on the improvement of students' schistosomiasis cognitive level, the same results were obtained in some similar researches conducted in Brazil and Nigeria [30,31]. On the contrary, some non-interactive health education modes are not effective [20].…”
Section: Discussionsupporting
confidence: 61%
“…Through the implementation of schistosomiasis health education session, the cognition level of schistosomiasis among primary and secondary school students was significantly improved, and the effect on primary and secondary school students was quite. This suggested that This interactive mode health education has a positive effect on the improvement of students' schistosomiasis cognitive level, the same results were obtained in some similar researches conducted in Brazil and Nigeria [30,31]. On the contrary, some non-interactive health education modes are not effective [20].…”
Section: Discussionsupporting
confidence: 61%
“…Raising awareness about NTDs can serve as a powerful affordable intervention for infection control. Also, the high level of awareness is capable of achieving significant and long-lasting results in controlling these diseases [18,19]. There are only few studies in literature assessing the knowledge of medical and nursing students about NTDs; especially in the developing countries [17].…”
Section: Discussionmentioning
confidence: 99%
“…Approvals were also obtained from the epidemiology course coordinator in the Faculty of Nursing, Cairo University and the head of public health department in the Faculty of Medicine, Cairo University before the study conduction. The Research Ethics Committee of Faculty of Medicine, Cairo University approved the study (N-39- 19).…”
Section: Ethics Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The health department can conduct related essay competitions, snail-survey activities and other activities every year, so that to deepen students' understanding of schistosomiasis. The health department should develop more publicity materials and products [28], through which these knowledge of schistosomiasis prevention and control will reach thousands of families. Students' health education should be constantly carried out and persevered, and the students' cognitive level should be improved through long-term indoctrination.…”
Section: Discussionmentioning
confidence: 99%